PENGARUH PEMBIAYAAN MURĀBAḤAH DAN IJĀRAH TERHADAP KESEJAHTERAAN NASABAH - Mufidah, Atin; Abd Muhaimin, Abdul Wahab; Khan, Dawud Arif (Cattleya Darmaya Fortuna, 2024)
The creation of services and products to meet community requirements has been prompted by the swift growth of Islamic banking and non-banking Islamic financial institutions. Before 1997, the only financial products available to Islamic banking institutions and Islamic microfinance organizations for fundraising purposes were current accounts, savings accounts, and deposits. Islamic financial organizations like murābaḥah, murābaḥah, ijārah, musyarakah, and others execute a lot of financing contracts. The author of this thesis focuses on how ijarah and murābaḥah are financed. The goal of this thesis is to examine the impact of financing for ijārah and murābaḥah on the well-being of Syariah Berkah Cemerlang Cooperative, Bogor, as well as the impact of financing for these factors either concurrently or simultaneously on the well-being of customers in the Bogor Berkah Cemerlang Syariah Cooperative. This study uses a quantitative approach to descriptive analysis. In order to test the established hypotheses, data is collected via research tools, analyzed quantitatively and statistically, and supplemented with interviews to relevant parties.The Qur'an and Al-hadith, Fatwa DSN MUI, a number of periodicals, and an analysis of research findings from questionnaires and interviews served as the key sources of data for this study. This study's secondary data consists of a number of books and illustrative articles about murābaḥah and ijārah. Based on the study's findings, it can be said that ijārah and murābaḥah financing have a simultaneous and significant positive impact on the welfare of the Syariah Berkah Cemerlang Cooperative's Clients in Cibinong Bogor.